EFEKTIFITAS PROGRAM TAMBAHAN DALAM MENINGKATKAN KEMAMPUAN PENGENALAN MEMBACA PADA ANAK KELOMPOK B DI TK ISLAM PLUS AL MUCHLISIN - Nina Nuriyah Ma’arif; Wahyu Safarina (Atthiflah: Journal of Early Childhood Islamic Education, 2022)
This article aims to examine the effectiveness of the additional class program in improving group B grade students' early reading skills at Islamic Kindergarten Plus Al Muchlisin in Gresik city, as well as its influence factors. Using a descriptive qualitative approach, the findings illustrate that the additional program is quite effective in improving the ability to read in early childhood students. The evidence is that all students (20 children) who are involved in this program are able to "develop according to expectations (BSH)". In this regard, this additional program is carried out through beginning reading lesson activities, scheduling the time for the implementation of early reading lessons, and conducting the evaluation process as well. The factors that encourage the effectiveness of the additional class program in flourishing group B grade students' reading skills at Islamic Kindergarten Plus Al Muchlisin, include the motivational spirit of the students themselves, the enthusiasm of students' interest in learning to read, and fully support from parents.